1984
DOI: 10.1111/j.1468-2338.1984.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade union education: its past and future

Abstract: In this article the author examines how the TUC Education Service was established and assesses the achievements of its regional scheme in meeting the educational needs of trade unionists. The focus is on the problems of conflict and compromise over provision, together with the relationship between educational institutions, the state and trade unions.HIS article examines how the TUC Edu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A recent study has confirmed that such provision is particularly beneficial in supporting the workplace actions of health and safety representatives . From the mid-1970s, when, as part of the Social Contract, the Labour government made public funds available for trade union education, a significant proportion of this training was resourced by funding from the state (Smith, 1984). However, the history of this resourcing has been fraught with uncertainties concerning both its level and continuity.…”
Section: Safety Representative Trainingmentioning
confidence: 99%
“…A recent study has confirmed that such provision is particularly beneficial in supporting the workplace actions of health and safety representatives . From the mid-1970s, when, as part of the Social Contract, the Labour government made public funds available for trade union education, a significant proportion of this training was resourced by funding from the state (Smith, 1984). However, the history of this resourcing has been fraught with uncertainties concerning both its level and continuity.…”
Section: Safety Representative Trainingmentioning
confidence: 99%
“…Labour education in Europe has a long association with the political aims of the left and with the policies and organization of trade unions in most European countries. At the same time it also has roots in the development of liberal adult education and, more recently, it has come to include elements that overlap significantly with definitions of vocational training [13]. This approach to health and safety education is reflected in the observation that:…”
Section: Parallels In the Approaches To Training In Health And Safety In Britain And Other Countries In Northern Europementioning
confidence: 99%
“…The studies that have been carried out by researchers outside the trade unions have generally been of small samples of shop stewards who have followed TUC courses, although safety representatives or shop stewards who were also safety representatives were included among the respondents in some of these studies [13,[37][38][39]. They all report findings that indicate positive responses to training, where respondents claim training has improved their ability to represent trade union members, they have found the courses they have attended "useful" and some change in the relationship of the participants with their workplace constituencies having resulted.…”
Section: The Role Of Trade Union Training In Supporting Health and Safety Representative Actionmentioning
confidence: 99%
“…But much of this movement lay outside of the universities -study circles and Folk High Schools in Scandinavia, the Mechanics Institutes in the UK, the Workers Education Association (WEA) in many countries, trade union education in Italy and elsewhere, and so on. Such adult education movements were linked to some of the streams of power of the day, particularly the labour movements and trade unions (Ruddock, 1980;Smith, 1984).…”
Section: Uk University Adult Educationmentioning
confidence: 99%
“…Much the same was true of women's education; in other sectors of adult education, these programmes were alleged to attempt to assist women to tackle their immediate (strategic) problems rather than the structural social questions of gender. As Smith suggested in another context, 'By being so narrowly conceived, [these nonuniversity training] courses do not provide for the broader educational needs of [the students]' (Smith, 1984). It was precisely these points which university adult education set out to remedy by using both theory and practice together, applied in specific local situations to specific issues.…”
mentioning
confidence: 99%